Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3727/096504013x13589503482734
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-375 Is Downregulated in Pancreatic Cancer and Inhibits Cell Proliferation In Vitro

Abstract: MicroRNAs (miRNAs) have emerged as important regulators in the development of pancreatic cancer and may be a valuable therapeutic application. Aberrant expression of microRNA-375 (miR-375) has been reported to be involved in development and progression in various types of cancers, but few studies have been conducted to determine its relationship with pancreatic cancer. Quantitative RT-PCR was used to detect the levels of miR-375 expression in pancreatic cancer tissue samples and cells. The cell growth rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…In addition, miR-375 is involved in maintaining mouse pancreatic α and β cell mass [24]. Previous studies indicated that the expression of miR-375 is down-regulated in human pancreatic cancer, squamous cell carcinoma, liver cancer, adenocarcinoma of the esophagus and gastric carcinomas, ectopic expression of miR-375 disturbed the proliferation of these cancer cells [25,26,27]. Based on the above findings that YAP1 was the target of miR-375 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, miR-375 is involved in maintaining mouse pancreatic α and β cell mass [24]. Previous studies indicated that the expression of miR-375 is down-regulated in human pancreatic cancer, squamous cell carcinoma, liver cancer, adenocarcinoma of the esophagus and gastric carcinomas, ectopic expression of miR-375 disturbed the proliferation of these cancer cells [25,26,27]. Based on the above findings that YAP1 was the target of miR-375 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By base-pairing with the complementary sites in the 3′untranslated region (3′UTR) of the mRNA, miRNAs regulate target genes by increasing mRNA decay or repressing translation [1921]. Growing evidences indicate that miRNAs control many cellular processes, including cell development, differentiation, proliferation and apoptosis [2227].…”
Section: Introductionmentioning
confidence: 99%
“…Also, many of these miRNAs have also been identified as prognostic markers for other diseases (like, cancer) and other complications associated with T2DM (including atherosclerosis, renal injury, non-alcoholic fatty liver disease, etc.). For example, in addition to being identified as a marker for T2DM, miR-375 is downregulated in pancreatic cancer and overexpression of miR-375 impacts cell proliferation, cell cycle distribution and apoptosis of pancreatic cancer cells [67]. Additionally, miR-375 also targets cancer-related proteins -caveolin1, JAK2 and YAP1 [57].…”
Section: Exosomes and Microvesiclesmentioning
confidence: 98%